Identification of Pituitary-Specific Transcription Factor-1 (PIT-1) Genotype in Bali Cattle - Muhammad Affan Muin; A. Supriyantono (Universitas Bengkulu, 2022)
This study aimed to identify the genotype of the gene Pituitary-specific transcription factor 1 (Pit-1) in Bali cattle (Bos sondaicus). A total of 20 cows Bali (13 males and 7 females) were used in this study. DNA samples isolated from blood samples using phenol-chloroform extraction method (Sambrook et al., 1989). This study using PCR-RFLP method. Amplification of specific DNA fragments (size 451 bp, intron regions stretching from 4 to exon 6) of the Pit-1 gene Bali cattle samples was performed using a pair of specific primers (forward: 5'-AAA-CCA-TCA-TCT-CCC-TTC-TT -3 ', and reverse: 5'-AAT-GTA-CAA-TGT-GCC-TTC-TGA-G-3'). Based on the results of RFLP analysis/HinfI was found that all of Bali cattle research resulted banding pattern uniform (monomorphic), the band size 244 bp and 207 bp, and the band patterns thus identified as genotype BB, so it is known that the frequency of A and B alleles at 0 and 1. The frequency of A allele was not found in Bali cattle (Bos sondaicus) showed a significant difference with other cattle breeds (Bos taurus and Bos indicus).